2018
DOI: 10.1007/s00415-018-8781-3
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the first event in pediatric acquired demyelinating syndromes with antibodies to myelin oligodendrocyte glycoprotein

Abstract: Antibodies against the myelin oligodendrocyte glycoprotein (MOG-Ab) can be detected in various pediatric acquired demyelinating syndromes (ADS). Here, we analyze the spectrum of neuroradiologic findings in children with MOG-Ab and a first demyelinating event. The cerebral and spinal MRI of 69 children with different ADS was assessed in regard to the distribution and characteristics of lesions. Children with acute disseminated encephalomyelitis (n = 36) or neuromyelitis optica spectrum disorder (n = 5) presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 27 publications
11
85
0
Order By: Relevance
“…[1][2][3][4] Furthermore, a similar MRI pattern in particular in the myelon can be seen in the ADEM or LETM associated with oligodendrocyte glycoprotein antibodies. 5 In conclusion, this is a typical AQP4-IgG positive case of neuromyelitis optica spectrum disorders (NMOSD) 6 in which peculiar bright spotty lesions (►Fig. 1E), which probably reflect intense damage of the cervical spinal cord, 2 are shown.…”
mentioning
confidence: 75%
“…[1][2][3][4] Furthermore, a similar MRI pattern in particular in the myelon can be seen in the ADEM or LETM associated with oligodendrocyte glycoprotein antibodies. 5 In conclusion, this is a typical AQP4-IgG positive case of neuromyelitis optica spectrum disorders (NMOSD) 6 in which peculiar bright spotty lesions (►Fig. 1E), which probably reflect intense damage of the cervical spinal cord, 2 are shown.…”
mentioning
confidence: 75%
“…In MOG antibody-associated ON, typical imaging characteristics are a contrast enhancement of the optic nerve, a perineural enhancement in a proportion of the patients, and in 80%, more than half of the pre-chiasmic optic nerve length being affected ( 79 , 65 ). Lesion distribution in children seems to be age-dependent, with poorly demarcated, widespread lesions in younger children, in contrast with a normal brain MRI in older children ( 80 ). It has been possible to distinguish MOG antibody-associated NMOSD from MS with a specificity of 95% and a sensitivity of 91% by employing predefined MRI criteria for lesion distribution, including Dawson's fingers, subcortical U fiber lesions, and lesions adjacent to the lateral ventricles, as typical for MS ( 81 ).…”
Section: Paraclinical Findings and Mog Antibodiesmentioning
confidence: 99%
“…It was reported that ADEM cases with MOG antibody had a certain MRI feature (large, hazy or bilateral brain lesions), which was significantly different from MOG antibody negative cases. 32 In a pediatric cohort study of demyelinating disease patients (n = 210), MOG antibodies were positive in ADEM (57%) and less frequent in NMOSD (25%), clinically isolated syndrome (25%) and MS (8%). 33 In this cohort, ADEM had higher MOG antibody titers in patients with younger onset (aged <10 years, median 7 years), whereas pediatric MS occurred at older ages (median 14 years) and MOG antibody was detected in just a few such cases with low titers.…”
Section: Adem In Mog Antibody-associated Diseasementioning
confidence: 96%
“…In MOG antibody‐associated diseases, common the clinical phenotypes are bilateral or isolated ON, ADEM and myelitis. It was reported that ADEM cases with MOG antibody had a certain MRI feature (large, hazy or bilateral brain lesions), which was significantly different from MOG antibody negative cases . In a pediatric cohort study of demyelinating disease patients ( n = 210), MOG antibodies were positive in ADEM (57%) and less frequent in NMOSD (25%), clinically isolated syndrome (25%) and MS (8%) .…”
Section: Mog Antibody‐associated Disseminated Demyelinating Diseasesmentioning
confidence: 97%
See 1 more Smart Citation